Comparative in vitro Quality Evaluation of Brands of Propranolol Hydrochloride Tablets Available in the Libyan Market - Muftah, Eman; Almani, Fathia; Al Masoufil, Maram; Al hamrouny, Nawras (AlQalam Journal of Medical and Applied Sciences, 2025)
Propranolol, a beta-blocker, is used in the management of cardiovascular conditions such as irregular heart rate and high blood pressure. The study was carried out to examine the in vitro quality control tests for four brands of propranolol hydrochloride 10 mg tablets, sold in community pharmacies in Tripoli, Libya. The parameters determined were identification, weight variation, friability, hardness, disintegration, dissolution rate, and assay of the tablets. The tablets were evaluated for conformity with USP and BP specifications. Results obtained showed that tablet weight in the range of 51.2 ±1.03mg to 150.1±1.60mg, friability of < 1 % for all brands, hardness ranged from 3.406±3.41 to 6.122±0.47 kg/cm2, disintegration time of 0.8 ± 0.37 to 7.62 ± 0.47minutes, whereby one brand is uncoated tablets and assay of 90.41±0.038 to 109.90 ±0.011% with two brands deviating from the specified limit. The four brands also released more than 80% of their drug content within 30 minutes. Analysis of similarity factor f2 and difference factor f1, revealed that none of the brands can be interchangeable with brand A in terms of dissolution profile in 0.1 M HCl and in phosphate buffer (pH 6.8). The study showed that propranolol samples examined passed all the Pharmacopoeial tests for satisfactory quality except specifications of drug content, where brand A and brand C did not comply with the Pharmacopoeial limits. Thus, not all brands can be used interchangeably in clinical practice.